2016
DOI: 10.1097/iae.0000000000001142
|View full text |Cite
|
Sign up to set email alerts
|

Metaanalysis of Real-World Outcomes of Intravitreal Ranibizumab for the Treatment of Neovascular Age-Related Macular Degeneration

Abstract: PURPOSE: To report the efficacy and safety of intravitreal ranibizumab for neovascular agerelated macular degeneration (nAMD) in real-world practice. METHODS: Metaanalysis of 26,360 patients from 42 real-world observational studies reporting outcomes of intravitreal ranibizumab for nAMD published between 2007 and 2015. Baseline demographics, lesion type, and visual acuity (VA) were recorded. The weighted mean was calculated for change in VA and frequency of injections and visits during year 1, year 2, and 3 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
161
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 54 publications
21
161
2
1
Order By: Relevance
“…The 12 month visual outcomes between the 2Q4 (12 injections) and 2Q8 (eight injections) aflibercept arms were similar in the VIEW 1 and 2 clinical trials, however the data here suggest that there can be a significant decline in visual outcomes with a further reduction in injection frequency, especially when fewer than seven injections are delivered in year 1 . A similar association between reduced anti‐VEGF injection frequency and worse visual acuity outcomes has been identified in a global meta‐analysis of real‐world outcomes of ranibizumab for nAMD …”
Section: Discussionsupporting
confidence: 71%
“…The 12 month visual outcomes between the 2Q4 (12 injections) and 2Q8 (eight injections) aflibercept arms were similar in the VIEW 1 and 2 clinical trials, however the data here suggest that there can be a significant decline in visual outcomes with a further reduction in injection frequency, especially when fewer than seven injections are delivered in year 1 . A similar association between reduced anti‐VEGF injection frequency and worse visual acuity outcomes has been identified in a global meta‐analysis of real‐world outcomes of ranibizumab for nAMD …”
Section: Discussionsupporting
confidence: 71%
“…The incidence of SAE with commonly used anti-VEGF drugs ranges from 0.6% to 2.7% in major clinical trials 6 21 22. In a meta-analysis that included 26 360 patients from 42 ‘real life’ nAMD studies, Kim et al 22 reported TEE and death rates of 0.6% and 0.7%, respectively. The lower incidences of adverse events from these studies, compared with those reported in randomised control trials, may be due to incomplete capture of data.…”
Section: Discussionmentioning
confidence: 99%
“…Although this sample size was relatively small, these outcomes are comparable to the early outcomes achieved by treatment-naïve patients on a T&E regimen in other randomised, controlled and real-world studies [9, 10, 13, 26]. It is anticipated that the sample size of this cohort will increase following the end of data collection for the full retrospective and prospective observational components of the TERRA study.…”
Section: Discussionmentioning
confidence: 61%